Postoperative Computed Tomography Evaluation of Posterior Tibial Plateau Fractures: Mean 7-Year Clinical Follow-Up - Li, Dongzhe; Fang, Yue; Liang, Yu; Ma, Kunlong; Zou, Chang (The Journal of Knee Surgery, 2018)
The aim is to assess the association between computed tomography (CT) findings and clinical outcomes in posterior tibial plateau fractures (TPF). This is a retrospective analysis of the records of 23 patients with posterior TPF treated at our institution between 2004 and 2011. Two indices of residual articular displacement of posterior TPF (gap and step-off) were measured from CT images, and clinical outcomes were assessed using the Short Musculoskeletal Function Assessment (SMFA) questionnaire. Spearman's rank correlation coefficient analysis was used to evaluate the correlations between the postoperative posterior TPF radiological findings and the clinical outcomes. Both the intraobserver and the interobserver correlation coefficients were high (0.90 and 0.92, respectively), indicating excellent agreement between the reviewers for the assessment of residual displacement via CT scans. Additionally, residual articular step displacement showed a strongly negative correlation with clinical outcomes (R = 0.700, p = 0.036), whereas the residual gap displacement did not (R = 0.400, p = 0.505). More importantly, the medial posterior step displacement was significantly correlated with the clinical outcomes (p = 0.040), whereas the lateral posterior step displacement was not (p = 0.618). Based on the data of this study, the higher the step-off deformity of the medial posterior tibial plateau, the worse the SMFA. More attention should be paid to this factor when treating medial posterior TPF.
Keywords: tibial plateau fracture; clinical outcomes; computed tomography